NLRX1 Modulates Immunometabolic Mechanisms Controlling the Host–Gut Microbiota Interactions during Inflammatory Bowel Disease - Leber, Andrew; Hontecillas, Raquel; Tubau-Juni, Nuria; Zoccoli-Rodriguez, Victoria; Abedi, Vida; Bassaganya-Riera, Josep (Frontiers in Immunology, 2018)
Interactions among the gut microbiome, dysregulated immune responses, and genetic factors contribute to the pathogenesis of inflammatory bowel disease (IBD). Nlrx1-/- mice have exacerbated disease severity, colonic lesions, and increased inflammatory markers. Global transcriptomic analyses demonstrate enhanced mucosal antimicrobial defense response, chemokine and cytokine expression, and epithelial cell metabolism in colitic Nlrx1-/- mice compared to wild-type (WT) mice. Cell-specificity studies using cre-lox mice demonstrate that the loss of NLRX1 in intestinal epithelial cells (IEC) recapitulate the increased sensitivity to DSS colitis observed in whole body Nlrx1-/- mice. Further, organoid cultures of Nlrx1-/- and WT epithelial cells confirm the altered patterns of proliferation, amino acid metabolism and tight junction expression. These differences in IEC behavior can impact the composition of the microbiome. Microbiome analyses demonstrate that colitogenic bacterial taxa such as Veillonella and Clostridiales, are increased in abundance in Nlrx1-/- mice and in WT mice co-housed with Nlrx1-/- mice. The transfer of an Nlrx1-/- associated gut microbiome through co-housing worsens disease in WT mice confirming the contributions of the microbiome to the Nlrx1-/- phenotype. To validate NLRX1 effects on IEC metabolism mediate gut-microbiome interactions, restoration of WT glutamine metabolic profiles through either exogenous glutamine supplementation or administration of 6-diazo-5-oxo-l-norleucine abrogates differences in inflammation, microbiome and overall disease severity in Nlrx1-/- mice. The influence NLRX1 deficiency on SIRT1-mediated effects is identified to be an upstream controller of the Nlrx1-/- phenotype in intestinal epithelial cell function and metabolism. The altered IEC function and metabolisms leads to changes in barrier permeability and microbiome interactions, in turn, promoting greater translocation and inflammation and resulting in an increased disease severity. In conclusion, NLRX1 is an immunoregulatory molecule and a candidate modulator of the interplay between mucosal inflammation, metabolism and the gut microbiome during IBD.